A Study on Masculinity: "A Cheerleader Boy is girlies? I don't give a care" - Inggraini Hartono; Matheus Yumarnamto (ELITE JOURNAL, 2022)
This paper studies the masculinity discourses emerging in the perception of a cheerleader boy and his friends. The boy is an active cheerleader’s member who also train some other cheerleaders. This study aimed to find out (1) how a cheerleader boy perceives the idea of masculinity and (2) how the closest person thinks of him as a cheerleader boy. Using the three theoretical tools of inquiry suggested by Gee (2005) for critical discourse analysis (1) Identity, (2) Discourse, and (3) Perspectives, several themes are found from the interview with Bob, the cheerleader boy and Anna, his close friend. They are (1) Come join, (2) It’s another competition, (3) I don’t give a care, (4) Dance is a matter of art, (5) It depends on the person, (6) As long as you’re happy, (7) He’s a dancer. While from Nana’s perspective, I found two themes. They are (1) Cheerleader boy is cool and (2) easy-going and friendly.